Konsep Moderasi Islam dalam Pemikiran - Khairan Muhammad Arif (Millah: Journal of Religious Studies, 2020)
The current moderation of Islam has become a very important discourse in the lives of Muslims. The moderation of Islam which forms part of the original Islamic form of Islamic teachings, is hoped to bring the life of a better, just, superior and civilized Muslims. Moderation or Wasathiyah Islam is the main character of Islam taught by Allah in the Qur'an and also in the US-Sunnah. That this people is a moderate and middle people whom God has ever made in human circles. Therefore, the purpose of this study is to exploit and socialize these moderate Islamic teachings to the people of Indonesia and the world, so that Islam becomes a religion that becomes mercy for all nature. The writing methods in this study, using a library method and a classical and contemporary Islamic literacy approach. From here then analyzed in accordance with the context of the life of Muslims in Indonesia, especially in the aspect of Islamic thought developed in Indonesia. Results of this study. First: Giving birth to a moderate concept of Islamic thought to understanding and a moderate attitude in implementing Islam in accordance with the Qur'an and As-Sunnah. Second: Provide a clear distinction between moderate thinking and other Islamic thoughts.